Uninterrupted Anticoagulation With Catheter Ablation Feasible and Effective - Mosley, Mary (MD Conference Express, 2015)
In patients with nonvalvular atrial fibrillation who are undergoing catheter ablation, VENTURE AF has shown that uninterrupted rivaroxaban compared with uninterrupted warfarin is associated with a risk of periprocedural thromboembolic events and major bleeding that was similar to that seen with warfarin. An open-label multicenter registry with uninterrupted apixaban vs uninterrupted warfarin yielded the same result.